Ulcerative colitis complicated by primary sclerosing cholangitis and autoimmune hepatitis overlap syndrome: a case report and literature review - Zhang, Xinhe; Lin, Xuyong; Li, Xuedan; Guan, Lin; Li, Yiling; Wang, Ningning (Frontiers in Immunology, 2023)
Primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), and ulcerative colitis (UC) are immune diseases of the digestive system. Some patients develop overlap syndrome, the presentation of two or more of the clinical, biochemical, immunological, and histological features of these conditions simultaneously or sequentially. The incidence of UC in PSC-AIH overlap syndrome is as high as 50%. In contrast, PSC-AIH overlap syndrome is rare in UC patients. However, because it has a low prevalence and has been studied in less detail, PSC is often misdiagnosed as primary biliary cholangitis (PBC) in its early stage. Herein, we reported a case of a 38-year-old male patient who presented to a clinician in 2014 with irregular bowel habits. A colonoscopy suggested UC. In 2016, the patient was found to have abnormal liver function and was diagnosed with PBC by pathology. He was treated with ursodeoxycholic acid (UDCA) but this had no effect on his liver function. Additional liver biopsies in 2018 indicated PBC-AIH overlap syndrome. The patient refused hormone therapy for personal reasons. Following UDCA monotherapy, his liver function remained abnormal. The patient was reexamined after repeated abnormal liver function tests and bowel symptoms. Systematic laboratory testing, imaging diagnosis, colonoscopy, liver biopsy, and various pathological examinations conducted in 2021 were used to diagnose the patient with PSC-AIH-UC overlap syndrome. He was treated with various drugs, including UDCA, methylprednisolone, mycophenolate mofetil, and mesalazine. His liver function improved significantly after treatment and follow-up is ongoing. Our case report highlights the need to raise awareness about rare and difficult-to-diagnose clinical disorders.